Performance analysis of water flow window systems with thermal energy storage tank includes phase change material in autumn season - Yamac, Halil Ibrahim; Koca, Ahmet (Elsevier, 2023)
When it comes to solar energy systems, the phase change materials (PCM)s latent heat storage (LHS) capacities can be advantageous for thermal energy storage (TES). The Water or Liquid Flow Window (WFW-LFW) Systems are notions that have just recently gained popularity. Solar energy is dissipated and stored by water flow between the glazing panes. The experimental analysis of the WFW system, as well as solar energy storage using PCM acts like a heat exchanger numeri-cally, are made in this research (The volumes are around 2.4 L for water and 3.3 L for PCM in the tank). The experiment is carried out in a controlled environment, similar to prototype testing. Three identical test cabinets are used to assess the heating and cooling systems' electricity con-sumption of test cabinets. These are WFW with PCM tank, mains water-supported WFW, standard window (commercial air-filled). Two distinct PCMs are mounted in a water tank; they are filled in the tubes are positioned like a pistol-type. The windows have a surface area of about 0.3 m2. After comparison, the outcomes demonstrate that the ratios of cooling device consumption can be as low as 66% for daytime and the heating device consumption ratio can be as low as 12% for nighttime. The time of around 6 h for melting and 12 h for solidification of PCM is adequate.
Keywords: Water flow window; Phase change process; Thermal energy storage; Computational fluid dynamics; Solar energy